Union members in the armed forces, 1945 (1945)
1945 1939-1945 "Union members in the armed forces, 1945" [HFR0203], 1945 Workers could retain their union membership while in the armed forces. The National Union of Distributive and Allied Workers magazine, The New Dawn, offered a regular Forces Forum letter page for service members.